Estudo de tecnologias de aplicação e inseticidas para o controle de percevejos fitófagos na cultura da soja - Maziero, Heleno (2006)
The objectives of the study were: 1st to avaluate the effects of spray volume in application with flat fan nozzels on the efficacy of the insecticides endossulfan and tiamethoxan+lambdacyalotrin in the control of Piezodorus guildinii. 2nd to avaluate and compare the eficiency of the insecticides imidacloprid+betaciflutrin and thiametoxan+cypermethrin in the control of Nezara viridula by aerial application, using rotary disc atomizers, with and without using vegetal oil and ground application. 3rd to avaluate the efficiency of the insecticides imidacloprido+beta-ciflutrina, tiamethoxan+cipermetrina e endossulfan in the control of Nezara viridula by aerial application using rotary disc atomizers and hidraulic hollow cone nozzles. The inseticide tiamethoxan+lambdacyalotrin (21,15 + 15,90 g i.a. ha-1) has biger control of Piezodorus guildinii and residual effect than endossulfan (437,50 g i.a. ha-1). Tiamethoxan+lambdacyalotrin and endossulfan have the same behavior, improving Piezodorus guildinii control s with spray volume increasing. The aerial applications using rotary disc atomizers are more eficient when it is used vegetal oil as a carrier of the insecticides. Imidacloprid+betaciflutrin and thiametoxan+cypermethrin applied using rotary disc atomizers, with spray volume of 10 L ha-1, had equal eficiency than its graund application, with spray volume of 100 L ha-1. The effects of these insecticides reacted in the same way to the application technologies. Imidacloprido+beta-ciflutrina, tiamethoxan+cipermetrina e endossulfan are more eficient in the Nezara viridula control when applied using rotary disc atomizers Turbo Aero TA 88C5 than using hidraulic hollow cone nozzels D-6 and core 45.